2018
DOI: 10.1186/s12885-018-4765-z
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of KCTD12 to esophageal squamous cell carcinoma

Abstract: BackgroundIt has been shown that the expression of potassium channel tetramerization domain containing 12 (KCTD12) as a regulator of GABAB receptor signaling is reversely associated with gastrointestinal stromal tumors. In present study we examined the probable role of KCTD12 in regulation of several signaling pathways and chromatin remodelers in esophageal squamous cell carcinoma (ESCC).MethodsKCTD12 ectopic expression was done in KYSE30 cell line. Comparative quantitative real time PCR was used to assess the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 34 publications
(41 reference statements)
0
17
0
Order By: Relevance
“…This protein is one of the potassium channel tetramerization domain (KCTD) protein families that has a role as an auxiliary subunit of GABAB receptors to alter the emotionality and neuronal excitability [ 33 ]. The expression of KCTD12 transcript and protein was associated with multiple tumor types including gastrointestinal stromal, melanoma, and esophageal squamous cell [ 34 , 35 , 36 ]. Here, we report significant upregulation of KCTD12 in the KAIMRC1 cells in spite of the fact that previous proteomics-based results suggest downregulation of this protein in a breast cancer tissue isolated from a patient with invasive carcinoma [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…This protein is one of the potassium channel tetramerization domain (KCTD) protein families that has a role as an auxiliary subunit of GABAB receptors to alter the emotionality and neuronal excitability [ 33 ]. The expression of KCTD12 transcript and protein was associated with multiple tumor types including gastrointestinal stromal, melanoma, and esophageal squamous cell [ 34 , 35 , 36 ]. Here, we report significant upregulation of KCTD12 in the KAIMRC1 cells in spite of the fact that previous proteomics-based results suggest downregulation of this protein in a breast cancer tissue isolated from a patient with invasive carcinoma [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…11 Abbaszadegan et al showed that KCTD12 can suppress Wnt/Notch signaling, stem cell factors, and chromatin remodelers in esophageal squamous cell carcinoma. 12 Nonetheless, KCTD12 is dramatically upregulated and closely correlated with larger tumor sizes, higher pathologic stages, and poor survival in cervical and lung cancers. 13 especially, knockdown of FOXO1 can restore the inhibitory effect of KCTD12 on cell proliferation of breast cancer.…”
Section: Potassium Channel Tetramerization Domain Containing 12mentioning
confidence: 99%
“…Not only that KCTD12 plays an important suppressive function and its high level is related with favorable prognosis in gastrointestinal stromal tumors 11 . Abbaszadegan et al showed that KCTD12 can suppress Wnt/Notch signaling, stem cell factors, and chromatin remodelers in esophageal squamous cell carcinoma 12 . Nonetheless, KCTD12 is dramatically upregulated and closely correlated with larger tumor sizes, higher pathologic stages, and poor survival in cervical and lung cancers 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Earlier reports stated that KCTD12 inhibited CRC stemness and metastasis through suppressing the ERK pathway 5 . The latest study found that KCTD12 exerted its inhibitory role in ESCC through inhibiting stem cell factors 7 . However, the CSC hypothesis in melanoma is controversial 12,15 .…”
Section: Discussionmentioning
confidence: 99%
“…Earlier reports declared that KCTD12 promoted the proliferation of human uveal melanoma OCM-1 cells 6 . In addition, it was reported that KCTD12 acted as a tumor suppressor in esophageal squamous cell carcinoma (ESCC) through the WNT/NOTCH pathway and chromatin remodeling 7 . However, the role of KCTD12 in cutaneous melanoma progression has yet to be investigated.…”
Section: Introductionmentioning
confidence: 99%